A Comparative Evaluation Of Positional Accuracy Of Parallel Implant And Three Angulated Implants Using Open Tray Technique: An In Vitro Study - Mohsin, Sania; Shahi, Harendra; Sudheer, Arunachalam; Priya, Priya; Mondal, Susmita (Journal of Neonatal Surgery, 2025)
Aim: The aim of this in vitro study is to evaluate and compare the positional accuracy of parallel implants and angulated implants placed at 15°, 20°, and 25° using the open tray impression technique. Objective: The objectives of this study are to evaluate and compare the positional accuracy of parallel implants with angulated implants placed at 15°, 20°, and 25°, using polyether as the impression material and pattern resin as the splinting material. Specifically, the study aims to assess the accuracy of parallel implants against each angulated group individually and to compare the differences in positional accuracy among the three angulated groups to determine the effect of increasing implant angulation on impression precision. Materials and methods: The present study was conducted in the Department of Prosthodontics and Crown & Bridge at Mithila Minority Dental College and Hospital, Darbhanga, Bihar. It aimed to evaluate the accuracy of implant positioning across different angulations using a Visual Coordinate Measuring Machine (VCMM).A total of four custom-made acrylic resin test models were fabricated using a standardized silicone edentulous maxillary mold. Each model was processed with heat-cure acrylic resin to ensure uniformity in dimensions. Six implants were placed bilaterally in each model at the lateral incisor, first premolar, and second molar regions using a surgical guide to standardize positioning and angulation. A micromotor was employed to control implant angulations accurately.In Model 1, all implants were placed parallel to each other and perpendicular to the horizontal plane. In Model 2, the lateral implants were inclined mesiobuccally at 15°, the premolar implants remained upright, and the molar implants were distally inclined at 15°. Model 3 followed the same configuration as Model 2, but with 20° inclinations, while Model 4 had 25° inclinations at the lateral and molar sites, with upright premolars. Once implant placement was complete, open tray impression copings were secured to the implants and splinted with dental floss and pattern resin to maintain their relative positions. A total of 21 impressions were taken for each test model using the open tray technique. Custom trays were fabricated for each impression, and tray adhesive was applied to the intaglio surface prior to impression making with polyether material. Master casts were poured using Type IV dental stone and were allowed to set for 60 minutes before retrieval and trimming. Results: In this study, a total of 84 samples were equally distributed among four groups. Each group—Group I, Group II, Group III, and Group IV—comprised 21 samples, accounting for 25% of the total sample size. This equal distribution ensured consistency across all study groups for comparative evaluation. For Group I, the mean inter-implant distances were recorded at various points. The distance between points A and B ranged from 23.17 mm to 25.91 mm, with a mean of 25.03 mm and a standard deviation of 0.63 mm. The distance from B to C had a minimum of 13.20 mm and a maximum of 15.00 mm, with a mean value of 14.16 mm and a standard deviation of 0.46 mm. From C to D, the distances ranged between 22.96 mm and 24.95 mm, showing a mean of 24.22 mm and a standard deviation of 0.58 mm. Lastly, the distance from B to D varied between 32.59 mm and 36.12 mm, with a mean distance of 34.71 mm and a standard deviation of 0.91 mm.Bottom of Form Conclusion: Implants placed at higher angulations—such as 25 degrees or more—can lead to significant discrepancies in the positional accuracy of multiple implants on the definitive cast. This deviation often compromises the passive fit of the final prosthesis, especially in full-arch rehabilitations such as All-on-4 and All-on-6. A lack of passive fit can result in mechanical complications, increased stress on the prosthetic components, and reduced long-term success of the restoration. To achieve an accurate and stable passive fit, implant angulations in All-on-4 and All-on-6 cases should ideally range between 15 and 20 degrees. Positional inaccuracies within this range are generally manageable using standard angled abutments. However, when implant angulation exceeds 25 degrees, corrections become more complex and require custom CAD/CAM abutments or specialized multi-unit abutments. Although cone-shaped multi-unit abutments offer a solution for correcting angulation and improving parallelism, they present certain limitations. The most notable drawback is the use of a very small prosthetic screw, which can be difficult to handle and tighten securely. In cases of poor alignment, additional manufactured caps and securing screws may be needed to achieve a passive prosthetic bridge fit—adding to both technical complexity and financial costs. Therefore, to minimize such challenges and ensure optimal prosthetic outcomes, clinicians are recommended to limit implant angulations to below 25 degrees in full-arch restorations. This approach simplifies prosthetic planning, enhances passive fit, and improves overall treatment predictability and patient satisfaction